Cirebon Melet: Smart Society - Permata, Mochamad Rizky; Aditya , Reynanda Rizky; Wulandari, Sri; Lestari, Aghnia Dian (Indonesian Journal of Advanced Research, 2024)
The rapid development of technology provides easy access to information. The success of the community in utilizing the internet optimally is the key to realizing a Smart City. Smart City in Cirebon City has one of the programs called "Cirebon Internet Literate". This program is carried out by the Cirebon City Information and Statistics Communication Office (DKIS). This program provides free Internet services in public areas and provides socialization to the public about digital literacy. The formulation of the problem in this study is how to implement the Cirebon Melet Program policy. The research method used is a qualitative research method with a descriptive method. which includes data reduction, data presentation, and conclusion drawn. Data collection was carried out by means of interviews and observations at the Cirebon City Information Communication and Statistics Office (DKIS). The purpose of the research is to find out how the Cirebon Melet Program Implementation Policy is running effectively. The results of this study show that the implementation of the Cirebon Melet Program Policy Implementation has been running but is still not optimal, because there are factors that affect due to limited Internet access so that wifi coverage is not evenly distributed throughout the Cirebon City area, inadequate infrastructure because the infrastructure to support the Cirebon Internet Literacy program is still limited.